Electronic Raman scattering through a stripe ordering transition in La₂₋xSrxNiO₄ - Gnezdilov, V.P.; Pashkevich, Yu. G.; Yeremenko, A.V.; Lemmens, P.; Güntherodt, G.; Tranquada, J.M.; Buttrey, D.J.; Nakajima, K. (Физика низких температур, 2002)
We describe the results of electronic Raman scattering experiments in two differently doped single crystals of La₂₋xSrxNiO₄ (x=0.225 and 1/3). In B₁g symmetry a crossover from weakly interacting to pseudogap-like behavior is observed at a charge-ordering temperature Tco. In B₂g symmetry a redistribution of electronic continua with decreasing temperature is accompanied by a loss of spectral weight below Tco in the low-frequency region due to opening of a pseudogap. The slope of the Raman response at vanishing frequencies is investigated, too. Its temperature behavior in B₂g symmetry, which predominantly selects charge carriers with momenta along the diagonals of the NiO₂ bonds, provides clear evidence for one-dimensional charge transport in the charge-ordered phase.